Estimating individual total costs of domestic violence - Cristina Santos (The Open University, Economics Department, 2008)
This paper estimates total individual costs of domestic violence. It draws on a cross-section survey that includes data on self-reported victimization variables, individual income and a self-reported life satisfaction variable. Using a life satisfaction approach, it estimates the variation in income needed to compensate for the presence of domestic violence, approximating the shadow price of domestic violence. It accounts for socio-demographic characteristics, relative bargaining power, local crime rates and personality. Results show that the valuation respondents place on violence depends both on income and on whether they are men and women. Men's valuation tends to be more significant for low income levels and for low vulnerability levels. Women's valuation and marginal utility of income does not seem to depend significantly on violence. As such, women's average valuation is estimated to be approximately 12500 and men's goes from roughly 1000 up to 25000.
Keywords: D13; I18; J12; O15; 330; domestic violence; life satisfaction approach; shadow price; England and Wales; Privater Haushalt; Ehe; Gewalt; Soziale Kosten; England